Algorithm of Time and Frequency Remote Calibration System of SNSU-BSN - A. Mohamad Boynawan; Ratnaningsih Ratnaningsih; Windi Kurnia P; Yulita Ika P; Asep Hapiddin; Muhammad Azzumar (Faculty of Mathematics and Natural Sciences (FMIPA), Universitas Negeri Padang, Indonesia, 2020)
National Measurement Standards-National Standardization Agency of Indonesia (SNSU-BSN) as the National Metrology Institute of Indonesia has provided time and frequency calibration services for customers. Time and frequency equipment should be calibrated to traceable to the SI units. The calibration process can be carried out in a calibration laboratory. However, some measuring devices cannot be sent to the calibration laboratory. One of the devices that cannot be sent to the calibration laboratory is Cesium atomic clock. It must be calibrated to get the time difference with the local coordinated universal time (UTC), namely UTC(IDN). Therefore, to calibrate the Cesium atomic clock, a remote calibration method is needed. The remote system is also intended to conduct the calibration more effectively and efficiently. This method requires two Global Positioning System (GPS) receiver devices placed on the client-side and a calibration laboratory. For this reason, an algorithm for remote calibration has been developed. The algorithm has been tested to calibrate Cesium-3 of SNSU-BSN against UTC(IDN). The time difference between Cesium-3 and UTC(IDN) was 5.8 microseconds by using the algorithm. Based on the algorithm that has been built, it was concluded that the algorithm can be used to perform remote calibration for the related customer.